Revealing Synergies, Tensions, and Silences Between Preservation and Planning. Issue 2 (2nd April 2016) - Minner, Jennifer
Abstract : Problem, research strategy, and findings: Historic preservation and planning often operate together in the United States within local planning departments, sharing some common roots and a "fragile, uneasy alliance" (Birch & Roby, 1984 ). Over time, developments in both preservation and planning brought these disciplines and professions closer together, including shared concern for sustainability and common ground in community economic development, revitalization, land use planning, and urban design. Simultaneously, areas of tension and potential conflict emerged. Some preservation-oriented scholars and practitioners call for the expansion of preservation's sphere of influence and concern, while others caution of negative effects. In this literature review, I identify areas of confluence and friction, as well as silences and gaps, focusing especially on planning and preservation literature since the 1980s. Takeaway for practice: Few scholars have identified what planners and preservationists (and those who do both) can learn from one another, with some important exceptions. Planning scholarship can benefit from understanding how preservation has changed in tandem and in relation to planning. Preservationists can gain much from incorporating contemporary planning theory, especially with regard to participation and building an equity agenda for preservation that builds from preservation's strengths and recent advances toward recognizing a wider, more representative set of historic resources. Both planners and preservationists can benefit from stronger alliances in which scholars and practitioners engage in deeper dialogues and exchange. This interdisciplinary collaboration can unite leadership and vision with regard to equity and social justice, with deeper place-based knowledge to improve the social, environmental, and economic health of communities.